Acceleration of nanobainite transformation by multi-step ausforming process. (October 2015) - He, Jianguo; Zhao, Aimin; Zhi, Chao; Fan, Hongliang
Graphical abstract: Abstract : The effect of multi-step ausforming with small strain per pass (<10%) on the overall transformation kinetics, microstructures and tensile properties of a high carbon, silicon rich nanobainite steel was investigated. Nanobainite steel with bainite ferrite lath thickness of ∼50 nm, ultimate tensile strength of 2154 MPa and total elongation of 14% has been produced by being isothermally treated at 300 °C within 2 h after multi-step ausformed, in which, the multi-step ausforming process was modified with recovery treatment.